First Order Bernoulli Equations
Additional Examples
- We substitute $ y = v^{1/(1-2)} = v^{-1}$, so $ dy/dx = -v^{-2}dv/dx$, and our equation becomes $$ -v^{-2}\frac{dv}{dx} + v^{-1} = -6\exp(-2x)v^{-2} $$
- Multiply by $-v^{2}$ to obtain a linear equation in the usual form. $$ \frac{dv}{dx} - v = 6\exp(-2x) $$
- Solve the linear equation.
- Find the integrating factor $$ \mu(x) = \exp\left(\int -1 dx \right) = \exp(-x) $$
- Multiply through by the integrating factor $$ \exp(-x)\frac{dv}{dx} - \exp(-x)v = 6\exp(-2x)\exp(-x) = 6\exp(-3x) $$
- Recognize the left-hand-side as $\displaystyle \frac{d}{dx}(\mu(x)v).$ $$ \frac{d}{dx}(\exp(-x)v) =6exp(-3x) $$
- Integrate both sides. $$ \exp(-x)v = -2\exp(-3x) + C $$
- Divide through by $\mu(x)$ to solve for $ v.$ $$ v = -2\exp(-2x) + C\exp(x) $$
- Back substitute for $ y.$ $$ y = (-2\exp(-2x) + C\exp(x))^{-1} $$
- We check that $ y = 0$ is indeed a singular solution.
If you have any problems with this page, please contact bennett@math.ksu.edu.
©2010, 2014 Andrew G. Bennett